2006
DOI: 10.1007/s10048-006-0048-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility to Parkinson’s disease among South and North Indians: I. Role of polymorphisms in dopamine receptor and transporter genes and association of DRD4 120-bp duplication marker

Abstract: The depletion of dopamine levels in the brain due to degeneration of dopaminergic neurons of substantia nigra pars compacta is a hallmark of Parkinson's disease (PD). The cumulative contribution of genetic variations in genes from the dopaminergic pathway has been widely implicated to confer susceptibility to idiopathic PD. We present in this paper an extensive association analysis of a total of 20 markers including single nucleotide polymorphism/short tandem repeat/variable number tandem repeat/duplication ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Ours is the first study to include African Americans, but three other studies have examined the association of Taq1A and PD risk in Asian populations. Singh et al reported a decreased risk in PD among those who were homozygous for the Taq1A polymorphism (OR=0.3, 95% CI 0.1–1.0) [12], while another study in India [9] and one in Singapore [8] found no association.…”
Section: Discussionmentioning
confidence: 99%
“…Ours is the first study to include African Americans, but three other studies have examined the association of Taq1A and PD risk in Asian populations. Singh et al reported a decreased risk in PD among those who were homozygous for the Taq1A polymorphism (OR=0.3, 95% CI 0.1–1.0) [12], while another study in India [9] and one in Singapore [8] found no association.…”
Section: Discussionmentioning
confidence: 99%
“…[45] In India, candidate gene studies have been performed on SNCA, [46,47] Parkin, [48][49][50][51][52] PINK1, [53] DJ-1, [54,55] and LRRK2 [47,[56][57][58][59] only [ In India studies to understand the molecular basis of PD is rapidly getting pace. A number of association studies have been reported on the candidate [53,60] as well as the susceptibility genes involved in dopamine metabolism, [61][62][63] xenobiotic metabolism, [64,65] neuronal cytoskeletal stability [66,67] etc., from different parts of India. Recent genome wide association studies on Asian and Caucasian populations have identified a number of associated genes in PD including ethnicity specific susceptible genes.…”
Section: Genetics Of Movement Disordersmentioning
confidence: 99%
“…After estimation of statistic power, a variable number of tandem repeat located in 3′untranslated region (3′VNTR) and four SNPs (rs6347, rs3756450, rs2652510, rs2550956) were included in current combined-analysis, as listed in Table 1 [5,7,13,16,1820,2227,31,3336,3840,46,48,49]. There was lack of power for combined-analysis of other SLC6A3 polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…Studies with 3′VNTR have revealed some associations with the risk for PD. However, the association results have been conflicted [13,16,19,20,2224,26,27,33,36,38]. The confliction may underscore ethnic differences and poor power of detection in individual samples especially when the genetic effect is small.…”
Section: Discussionmentioning
confidence: 99%